Selection Method of Cross-Border e-Commerce Export Logistics Mode Based on Collaborative Filtering Algorithm - Ying Yang (Journal of Mathematics)
The combination of the Internet and foreign trade has promoted the rapid development of cross-border e-commerce, and cross-border e-commerce logistics has risen due to the development of cross-border e-commerce. However, the costs incurred by enterprises in the operation of intermediate logistics links have remained high for many years. Considering the cross-border electricity export logistics mode selection, the author of this paper tackles the main existing problems, using literature study, field survey method, case analysis and the collaborative filtering method of major consumer goods export logistics mode, and the advantages and disadvantages in the enterprise’ internal and external environmental analysis and evaluation, and puts forward a scientific logistics coordination mechanism and new export logistics mode. Firstly, the development background of cross-border e-commerce logistics is sorted out, and the research content, research method, and research framework are proposed based on the theoretical research of relevant scholars. Secondly, several logistics modes of cross-border e-commerce export are summarized, including international postal parcel, international express, international special line, etc., and the indicator system of logistics mode selection is determined through comparative analysis of application scope and advantages and disadvantages. Secondly, a logistics selection model based on collaborative filtering algorithm is constructed, and the model is verified by a practical case of a specific export cross-border e-commerce company. Finally, the research conclusions and application strategies of this paper are proposed, so as to provide the most appropriate logistics mode and guarantee suggestions for cross-border e-commerce enterprises and provide ideas and methods for cross-border e-commerce enterprises to choose international logistics mode for different types of import and export goods. The significance of this study was aimed at the current cross-border electricity development mainly by restricting factors, planning the most suitable for the development of China’s cross-border electronic business logistics mode, to some extent, and it has enriched the cross-border electricity business related research in the field of logistics, to inspire transformation of foreign trade enterprises, so as to better promote the cross-border electricity business healthy and orderly development and export logistics mode optimization selection.